Synthesis and characterization of a novel silica-niobia support for the immobilization of microbial fructosyltransferase aiming at fructooligosaccharides production. (June 2022) - Garcia, Leonardo Abreu; Prado, José Pedro Zanetti; Morales, Sergio Andres Villalba; Abreu Xavier, Michelle da Cunha; Lopes, Melina Savioli; da Silva, Elda Sabino; Maiorano, Alfredo Eduardo; Gunnewiek, Rodolfo Foster Klein; Perna, Rafael Firmani
Abstract: A new support for fructosyltransferase (FTase, E.C. 2.4.1.9) immobilization was obtained by a facile niobium deposition on powdered silica-gel, using a simple polymeric solution-based method, aiming to obtain a highly active biocatalyst for the production of fructooligosaccharides (FOS). The support was characterized by XRD, SEM, N2 physisorption, FTIR, TGA and DSC analyses. The support showed orthorhombic and monoclinic Nb2 O5 phases homogeneously distributed along the sample. The thermal decomposition of the organics yielded very fine particle sizes of a mixture of silica-niobia material with specific surface area of approximately 127 m² g −1 . FTIR analyses confirmed the presence of the immobilized enzyme. The immobilization yield and recovered activity of the enzyme were about 57.7% and 87.8%, respectively. It suggests a significant improvement in FTase adsorption on silica due to the addition of niobium and a high applicability of silica-niobia supports for FTase immobilization aiming at FOS production. Graphical Abstract: ga1 Highlights: A new material for successful FTase immobilization was synthesized. A silica-niobia solid was synthesized by a simple polymeric solution method. The orthorhombic and monoclinic Nb2O5 phases coexisted in the solid. The solid showed suitable surface area and composition for adsorption of FTase. The addition of Nb2O5 to silica improved the catalytic activity of the FTase.